NURSE'S ASSISTANCE IN HUMANIZING NATURAL CHILDBIRTH - Oliveira, Mayara Bárbara de (2024)
This study addresses the cruciality of the humanization of normal childbirth, focusing on women and their essential needs during childbirth. By valuing the choices, values, and desires of pregnant women, the aim is to offer comprehensive emotional and physical support, minimizing unnecessary interventions and promoting practices that respect the natural rhythm of labor. The research aims to demonstrate that humanization is not just a theoretical concept but a practical approach essential to ensuring dignity, respect, and individualized care during childbirth, transforming it into a meaningful and healthy experience. With the goal of exploring the benefits of this approach and the role of the nurse in its implementation, the study conducted a narrative literature review. The analysis focused on articles discussing natural and humanized childbirth from the nursing perspective, aiming to characterize the differences between cesarean and normal childbirth, the negative aspects of non-humanized birth experiences, and the importance of nursing in promoting a welcoming and empathetic environment. It is concluded that the humanization of childbirth, both normal and cesarean, is essential to ensuring a safe and respectful experience. The lack of humanization can lead to complications and negative impacts. The nurse plays a central role in implementing these practices, ensuring respect for the woman's autonomy and fostering a welcoming environment for childbirth.